2000
DOI: 10.4141/p99-139
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Canadian weeds. 8. Sinapis arvensis. L. (updated)

Abstract: . An updated review of biological information is provided for Sinapis arvensis L. Native to the Old World, the species is widely introduced and naturalized in temperate regions around the world. The species occurs in all the provinces, the Northwest Territories, and the Yukon. It is an important weed of field crops in the Canadian prairies. A strongly persistent seedbank, competitive annual growth habit and high fecundity all contribute to its weedy nature and ensure that it will be a continuing problem. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 98 publications
(112 reference statements)
2
43
0
Order By: Relevance
“…Naderi and Ghadiri [46] showed that oilseed rape production was negatively affected by an increased number of wild mustard plants per unit area. Although in our study, a reduction in the coverage of wild mustard was noted throughout the experiment with some post-emergence treatment, we confirm that this weed represents a thorny issue due to its great competitiveness [47,48]. In order to prevent seed yield losses, it would be necessary to adopt different agricultural practices to effectively tackle this weed.…”
Section: Methodssupporting
confidence: 52%
“…Naderi and Ghadiri [46] showed that oilseed rape production was negatively affected by an increased number of wild mustard plants per unit area. Although in our study, a reduction in the coverage of wild mustard was noted throughout the experiment with some post-emergence treatment, we confirm that this weed represents a thorny issue due to its great competitiveness [47,48]. In order to prevent seed yield losses, it would be necessary to adopt different agricultural practices to effectively tackle this weed.…”
Section: Methodssupporting
confidence: 52%
“…It has been reported that S. arvensis populations of 20-80 plants m -2 resulted in a reduction of 19 to 77% in canola yield (Warwick et al, 2000). There are also some reports on yield reduction in other crops as for example flax, potato, and cabbage (Zeinali & Ehteshami, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…There are also some reports on yield reduction in other crops as for example flax, potato, and cabbage (Zeinali & Ehteshami, 2004). The weedy and troublesome nature of S. arvensis are explained by its strongly persistent seed-bank, competitive growth habit, and high fecundity (Warwick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Sinapis arvensis is an annual or winter annual plant of the genus Sinapis [2]. S. arvensis is frequently found growing in Brassica napus and Triticum aestivum fields and is thought a kind of “poisonous weeds” for agricultural production [3].…”
Section: Introductionmentioning
confidence: 99%